DZIKIR NAFAS AL - GHAZALI DAN RELEVANSI KEHIDUPAN MASA SEKARANG - Syadza Afifah, Meika; Rafida Binti Abdul Rahim, Norhayati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Modern life today has the potential to make people lose the meaning of life because of the various demands of life that continue to develop rapidly. One effort to rediscover the meaning of life for a Muslim is to remember God again by doing dhikr. Breath dhikr is one of the spiritual practices that emphasizes the regulation and awareness of breathing in order to get closer to Allah SWT. According to Al-Ghazali, this dhikr is not just a repetition of words or sentences, but involves a deep appreciation of the greatness of Allah, which should be absorbed into every inhalation and exhalation. This study aims to see the relevance of breath dhikr in the lives of modern society today. This study uses a qualitative descriptive approach through library research whose data sources are obtained from books, notes, literature which in the writing system can be used to study or research an object. The results of this study indicate that with breath dhikr, a person can achieve inner peace and protect the heart from worldly thoughts. The practice of breath dhikr is in line with the needs of today's humans for mindfulness and meditation as a means of achieving balance between the material and spiritual worlds. In addition to providing peace of mind, breathing dhikr can also improve focus, productivity, and quality of life holistically. Thus, Al-Ghazali's teachings on breathing dhikr still have strong relevance as a method of spiritual and mental development in facing the challenges of modern life.